2021
DOI: 10.1186/s12875-021-01432-w
|View full text |Cite
|
Sign up to set email alerts
|

Improving the precision of depression diagnosis in general practice: a cluster-randomized trial

Abstract: Background Methods to enhance the accuracy of the depression diagnosis continues to be of relevance to clinicians. The primary aim of this study was to compare the diagnostic precision of two different diagnostic strategies using the Mini International Neuropsychiatric Interview (MINI) as a reference standard. A secondary aim was to evaluate accordance between depression severity found via MINI and mean Major Depression Inventory (MDI) sum-scores presented at referral. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…A recent Danish clinical study on the value of systematic psychometric testing, ie, no variation in use, did not find the diagnosis of depression to be more precise when based on psychometric testing compared with usual clinical assessment. 9 This finding was somewhat confirmed in this study, as we found no significant difference between groups with varying propensity for PT use for most of the investigated treatment outcomes. The finding of increased variation in the provided services has also been reported in other studies, with indications that some variation is non-negligible due to derived outcomes, such as the need for immediate identification and treatment of patients at risk of suicidal behavior after the loss of a loved one.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A recent Danish clinical study on the value of systematic psychometric testing, ie, no variation in use, did not find the diagnosis of depression to be more precise when based on psychometric testing compared with usual clinical assessment. 9 This finding was somewhat confirmed in this study, as we found no significant difference between groups with varying propensity for PT use for most of the investigated treatment outcomes. The finding of increased variation in the provided services has also been reported in other studies, with indications that some variation is non-negligible due to derived outcomes, such as the need for immediate identification and treatment of patients at risk of suicidal behavior after the loss of a loved one.…”
Section: Discussionsupporting
confidence: 81%
“…A recent clinical trial showed that systematic use of a depression-related PT did not increase the diagnostic precision compared with usual clinical assessment in Danish general practice. 9 Variation in health care and their influence on treatment outcomes are well documented. 10 , 11 A recent Danish study found an excess variation between Danish general practices in terms of the chronic care services provided, eg, talk therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Therefore, there is a need for accurate diagnostic tools. 5 The Danish clinical guidelines for general practitioners (GPs) recommend the use of the patient-reported outcome measure, the Major Depression Inventory (MDI) (Figure S1), to assist with identification and monitoring of depression severity in patients. 6 The MDI contains items that cover the spectrum of all ICD-10 and DSM IV symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with depression are identified and treated in general practice 3,4 . Therefore, there is a need for accurate diagnostic tools 5 . The Danish clinical guidelines for general practitioners (GPs) recommend the use of the patient‐reported outcome measure, the Major Depression Inventory (MDI) (Figure S1), to assist with identification and monitoring of depression severity in patients 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation